Past, Passivity, Passion: Deleuze's Allegorical Drama. Issue 1 (April 2019) - Borg, Ruben
Abstract : This article offers a rhetorical analysis of Deleuze's concept of the past, understood not as a modification of the present but as a pre-predicative, non-subjective articulation of time. Focusing on the discussion of the three passive syntheses of time in Chapter 2 of Difference and Repetition, it traces the continuity between past, passivity and passion across Deleuze's body of work in an effort not only to remark on the conceptual resonances between them, but, more importantly, to examine the figural and formal choices that codify those resonances, and to some extent over-determine them – in particular, Deleuze's recourse to allegory and tragic form. Though the past is constituted as a primordial component of time, it already exceeds itself in the passivity of that constitutive moment, of that originary gesture by which it is first committed to historical experience. The process is rendered in dramatic terms: Habitus and Mnemosyne (Habit and Memory; Present and Past) are first pitted against each other – respectively, as the origin of time and its ground. They are then overthrown by an unnamed third element 'which subordinates the other two to itself' and opens the whole to infinity. The article thematises the significance of the past within this allegorical drama, develops the character, and draws out the temporal structures encoded in Deleuze's figurations.